The Role of Genetics in Central Precocious Puberty: Confirmed and Potential Neuroendocrine Genetic and Epigenetic Contributors and Their Interactions with Endocrine Disrupting Chemicals (EDCs) - Andrea Mucci; Ethel Clemente (Endocrines, 2022)
Despite the growing prevalence of central precocious puberty (CPP), most cases are still diagnosed as “idiopathic” due to the lack of identifiable findings of other diagnostic etiology. We are gaining greater insight into some key genes affecting neurotransmitters and receptors and how they stimulate or inhibit gonadotropin-releasing hormone (GnRH) secretion, as well as transcriptional and epigenetic influences. Although the genetic contributions to pubertal regulation are more established in the hypogonadotropic hypogonadism (HH) literature, cases of CPP have provided the opportunity to learn more about its own genetic influences. There have been clinically confirmed cases of CPP associated with gene mutations in kisspeptin and its receptor (KISS1, KISS1R), Delta-like noncanonical Notch ligand 1 (DLK1), and the now most commonly identified genetic cause of CPP, makorin ring finger protein (MKRN3). In addition to these proven genetic causes, a number of other candidates continue to be evaluated. After reviewing the basic clinical aspects of puberty, we summarize what is known about the various genetic and epigenetic causes of CPP as well as discuss some of the potential effects of endocrine disrupting chemicals (EDCs) on some of these processes.